KAJIAN DAMPAK SOSIAL EKONOMI PEMBERDAYAAN NELAYAN DI DESA LIKUPANG DUA KECAMATAN LIKUPANG TIMUR KABUPATEN MINAHASA UTARA - Jamil, Muntaha (Universitas Sam Ratulangi, 2013)
Society Enableness represent the especial capital to develop the x'self and also maintain the kehidupanya in the middle of other society. Fisherman generally exploit the marine product is to live on. Condition of society of fisherman or society [of] coastal area represent the society group which [is] relative left behind economical, social ( specially in the case of accessing education and health service), and compared to [by] cultural [of] other society group. Condition of society of coastal area or fisherman society [of] various area [is] in general marked by existence of some characteristic, like poorness, situated behind [of] sosial-budaya, its[his] low [is] human resource ( SDM) [of] because most its resident only passing elementary school or finish not yet elementary school, and weaken the function nya from Group existence of[is Effort With ( KUB), Micro Financial Institution ( LKM), or organizational capacities [of] societyKeywords : fisherman, resource, enableness